DEVELOPING VOCABULARY MASTERY THROUGH GUESSING WORDS GAME FOR THE SEVENTH GRADE STUDENTS OF SMP NEGERI 10 PALU - Iftitah, Arika Nurul; Marzuki, Abdul Gafur; Kuliahana, Ana (Datokarama English Education Journal, 2020)
The objectives of this research was to know the process of learning English vocabulary by using guessing words game and to know the students’ problem in learning English vocabulary by using guessing words game for the seventh grade students of SMP Negeri 10 Palu in academic year of2019/2020 with the use of guessing words game technique. In this research, the researcher used qualitative research method. The researcher chose class VII D as sample which consisted of 23 students. In collecting the data, the researcher used four kinds of instruments, they were: observation,interview, test and document. Based on the observation, there are some problems in the teaching and learning. To solve those problems, the researcher implemented guessing words game as vocabulary activities. This research was conducted through classroom action research that consisted of two cycles. Each cycles consisted three meetings. The result of the research showed that there were some improvements of the students’ vocabulary. In cycle 1 average score was 62,86 there were some unsuccessful score. Meanwhile, in cycle 2 average score was 72,34 the implementation of guessing words game was successful in developing students vocabulary. Guessing words game gives better result to develop the students’ vocabulary. In other words, guessing words game is effective to use in teaching English vocabulary.